Recommendations for Evaluation and Management of Pain in Patients With Mucopolysaccharidosis in Latin America (2018)
The mucopolysaccharidosis (MPS) constitutes a heterogeneous group of rare genetic disorders caused by enzymatic deficiencies that lead to the accumulation of glycosaminoglycans. Several types of MPS are described, historically numbered from I to IX. Clinical observations strongly suggest the presence of chronic pain in patients with all types of MPS. There are few data in the literature on the evaluation and management of pain in these patients, a fact that can compromise the quality of life even more. Professionals with extensive experience in the care for patients with MPS held a meeting in April 2017 to discuss and propose recommendations for the evaluation and management of pain in patients with MPS in Latin America. This article summarizes the content of the discussions and presents the recommendations produced at the meeting. Patients with MPS present joint, bone, and muscle pain, as well as entrapment syndromes (spinal, optic nerve, carpal tunnel). The panel suggests the use of the following instruments for pain assessment: Face, Legs, Activity, Cry and Consolability Scale for children of up to four years of age and patients unable to communicate their pain; Child Health Assessment Questionnaire Scale; Facial Pain Scale and Numerical Pain Scale for patients of five to <18 years of age; Brief Pain Inventory and Short Form Health Survey 36 scales for patients aged 18 years or older. Based on the scores verified in these scales, the panel proposes pharmacological interventions for pain relief in this population of patients. © 2018 American Academy of Hospice and Palliative Medicine